Mesin Carnot Quantum dengan Dua Partikel Tidak Berinteraksi dan Tidak Berdekatan - Khazali Fahmi (Jurnal Teori dan Aplikasi Fisika, 2023)
In this article, we study the quantum Carnot engine using a one-dimensional infinite well potential model in which two particles are non-interacting, indistinguishable and have the same mass. We find that the efficiency of this model is the same as that of the one-dimensional infinite potential well model in which there is one particle. Moreover, efficiency can be measured only when L_C/L_A?2, where L_A and L_C are the potential well widths during isothermal and adiabatic expansion, respectively.